Perbedaan Rasio Neutrofil per Limfosit, Rasio Platelet per Limfosit dan Volume Platelet Rata-Rata pada Kehamilan dengan Preeklampsia dan Kehamilan Normal di RSUD Sanjiwani Gianyar - Ni Komang Surya Sanistiasih Budaya; I Made Pariartha; I Ketut Tangking Widarsa (Aesculapius Medical Journal, 2023)
Preeclampsia is an idiopathic multisystem disorder that affects 2-8% of pregnancies worldwide. It usually occurs after 20 weeks of pregnancy and affects both the mother and fetus. This study aims to determine the difference in the value of neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and mean platelet volume (MPV) between women with preeclampsia and normotensive pregnant women. This is a cross-sectional comparation study using patient’s medical record conducted in Sanjiwani Gianyar Public Hospital. The sampling technique used in this study is purposive sampling, with 60 samples in each group. The data collected then analyzed using SPSS for Windows by independent sampled-t-test. The result shows that the NLR, PLR and MPV values in women with preeclampsia were significantly different from normotensive pregnant woman. The NLR, PLR, and MPV values were found higher in women with preeclampsia, with mean difference value of 0.93 for the NLR variable (p=0.011), 21.97 for the PLR variable (p=0.011) and 0.47 for the MPV variable (p=0.008). The predictive value is seen from the effect size (Cohen's delta) where the three variables are included in the moderate category.